Digital skiguru - quantifying "ski feeling" using microsensors - Gløersen, Ø.; Hoel Rindal, O. M.; Tjønnås, J. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The performance of a cross-country (XC) ski is multifaceted and individual-specific. Consequently, ski-selection is often done by subjective assessment. Differentiating skis based on feeling is an arduous skill susceptible to individual bias. The aim of this study was to develop a sensor-based solution to augment subjective assessments of XC-skis.